The effects of fixed versus removable orthodontic retainers on stability and periodontal health: 4-year follow-up of a randomized controlled trial - Kamal Dhruvkumar Hotchandani; Janarthan Thangadurai; Akhilesh Singh Parate; Jeff Zacharia Nixon; Ranjit H Kamble; P Meghalapriya (Wolters Kluwer Medknow Publications, 2023)
Introduction: Long-term or even indefinite retention is routinely prescribed after orthodontic treatment as a preventive safeguard against post-treatment changes induced by tooth movement, physiological healing, and the aging process. Though both fixed and removable versions of retainers may be equally effective in terms of results, sufficient research to support this assumption is missing at the moment. Objectives: Long-term effects of fixed and removable retention on the periodontium, and the compliance level when used for an extended period of time. Methods: For 4 years participants were given a supply of canine-to-canine retainers and vacuum-formed canine-to-canine retainers. The inter-canine, as well as inter-molar widths, the length, and the extraction space opening of the mandibular anterior portion, were measured. Gingival inflammation, calculus, and plaque were observed, as well as the attachment of clinical and the case of bleeding during probing. 42 members had returned in the follow-up period, with 21 from each of the two groups. Measurements of the modified gingival index and plaque scoring were performed on the 10 intra-oral photographs that were taken at 4-week intervals in this study to investigate the intra-examiner reliability. Results: After controlling for confounding variables, there was a 1.64 mm (95% confidence interval [CI], 0.30, 2.98 mm) median between-groups difference among patients who utilized vacuum-formed retainers (VFRs). The treatment groups did not vary in inter-canine and intermolar widths (P = 0.52; 95% CI, −1.07, 1.05), arch length (P = 0.99; 95% CI, −1.15, 1.14), or opening of extraction spaces (P = 0.84). Conclusion: A long-term study demonstrates that fixed retention can preserve the alignment of the mandibular anterior over time for the first time. Gingival discomfort and higher plaque scores were reported in both types of retainers.